ANALISIS KOMUNIKASI PEMASARAN BISNIS ONLINE BUSANA MUSLIM ZISHEERI MELALUI MEDIA SOSIAL - Irawan, Dedi (Jurnal Signaling, 2024)
This research aims to analyze the marketing communication strategies used by the online Muslim fashion business Zisheeri through social media and identify the strengths and weaknesses of the Zisheeri brand's marketing communication strategies through social media. The research method used is qualitative to gain an in-depth understanding of the use of online media in marketing Muslim fashion. This research will conduct interviews with the owner of the online business brand Zisheeri. In addition, data analysis from social media platforms will also be conducted to observe trends and consumer behavior patterns related to Muslim fashion. The research results show that in establishing business communication for Zisheeri Muslim fashion, the brand has a strategy for building good relationships with consumers, with friendliness being the top priority of the Zisheeri brand. Consumers are free to ask anything about the Zisheeri fashion brand through chat on online media. Not only that, Brand Zisheeri often holds giveaways such as quizzes where everyone who wins will receive a prize. In addition, Zisheeri also provides an opportunity for its reseller partners to receive rewards in the form of Umrah packages as a token of appreciation for the established cooperation. However, this strategy can become ineffective if Zisheeri's target market is more active on other social media platforms besides Instagram and WhatsApp. The risk of giveaways, such as quizzes, making consumers dependent on prizes can reduce loyalty to Zisheeri's products.